ANALISIS POLA ASUH ORANG TUA YANG BEKERJA TERHADAP PEMBENTUKAN MORAL KEJUJURAN ANAK - Rosiana; Irfai Fathurohman; Mohammad Syaffruddin Kuryanto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to find out the parenting styles of working parents on shaping children’s honesty. This research used a qualitative approach and the type of case study research conducted at grade V SDN 3 Mayonglor, Kecamatan Mayong, Kabupaten Jepara. The respondents were students, their parents from several different occupations, and teachers. The data were collected thorugh unstructured observation, unstructured interview, and documentation. The data analysis used was descriptive qualitative data analysis. Based on the results of research, it was found that: 1) the parenting style in families with different types of work included: democratic and authoritarian. Whereas, with the regard to students’ moral, the researcher focused on honesty. It was found that the children’s honesty still needed to be improved. Thus, it was suggested for parents to provide appropriate parenting styles for the children to shape and improve the honesty for their children.